2015
DOI: 10.1021/jo502948t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of 2′-Deoxy-2′,4′-difluoroarabinose-Modified Nucleic Acids

Abstract: We report the synthesis, thermal stability, and RNase H substrate activity of 2′-deoxy-2′,4′-difluoroarabino-modified nucleic acids. 2′-Deoxy-2′,4′-difluoroarabinouridine (2,′4′-diF-araU) was prepared in a stereoselective way in six steps from 2′-deoxy-2′-fluoroarabinouridine (2′-F-araU). NMR analysis and quantum mechanical calculations at the nucleoside level reveal that introduction of 4′-fluorine introduces a strong bias toward the North conformation, despite the presence of the 2′-βF, which generally steer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…The therapeutic potential use of LNA (27) has led to the synthesis of a wide number of related analogues known as BNAs (bicyclic nucleic acids) (28). Our laboratory has had a long standing interest in nucleosides modified with fluorine at C2´ (11,(29)(30)(31)(32)(33) and more recently at both the C2´ and C4´ positions (34,35). 4´-Fluoro nucleosides are relatively unexplored in the literature, investigated in only a handful of studies (36)(37)(38)(39)(40), most of which encountered acid instability of the glycosidic linkage, which precluded these molecules from further studies and incorporation within oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic potential use of LNA (27) has led to the synthesis of a wide number of related analogues known as BNAs (bicyclic nucleic acids) (28). Our laboratory has had a long standing interest in nucleosides modified with fluorine at C2´ (11,(29)(30)(31)(32)(33) and more recently at both the C2´ and C4´ positions (34,35). 4´-Fluoro nucleosides are relatively unexplored in the literature, investigated in only a handful of studies (36)(37)(38)(39)(40), most of which encountered acid instability of the glycosidic linkage, which precluded these molecules from further studies and incorporation within oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Since the RNA-selective hybridization ability was highly related to the conformational preorganization of the sugar, we investigated the 1 H– 1 H J -coupling constants of H2″/H3′ and H1′/F2′ to determine the sugar conformation. According to the Karplus equation’s prediction [ 17 ], a northern conformer will have a large 3 J H2″H3′ coupling constant, whereas a southern conformer will have a large 3 J H1′F2′ value. The experimental 3 J H2″H3′ and 3 J H1′F2′ values of 2′-F,4′- C -OMe–araU in D 2 O were 5.6 and 9.0 Hz, respectively, whereas those for 2′-F–araU were 3.0 and 17.5 Hz, respectively ( Supplementary Materials, Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This conformational behavior is highly beneficial to the binding affinity to complementary RNA [ 15 , 16 ]. Moreover, Damha et al [ 17 ] demonstrated that introduction of 4′-F into 2′-F–araU switched the preferred sugar conformation from DNA-like to RNA-like by the similar anomeric effect of 4′-F. Hence, it was predicted that the 4′- C -alkoxy-2′-F–arabinonucleotide derivatives would also pre-organize the sugar ring toward a north conformation, and enhance the hybridization properties for antisense oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Also other fluorinated nucleic acids such as 2’-fluorocyclohexenyl nucleic acid (F-CeNA, Fig. 1) [27] and other modifications [2831] have been analyzed on their antisense properties.…”
Section: Introductionmentioning
confidence: 99%